Transactions on Engineering Technologies International MultiConference of Engineers and Computer Scientists 2013 - Yang, Gi-Chul.; Ao, Sio-Iong.; Huang, Xu.; Castillo, Oscar; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This volume contains revised and extended research articles written by prominent researchers participating in the international conference on Advances in Engineering Technologies and Physical Science was held in Hong Kong, 13-15 March, 2013. Topics covered include engineering physics, engineering mathematics, scientific computing, control theory, automation, artificial intelligence, electrical engineering, and industrial applications. The book offers the state of art of tremendous advances in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.
1 Statistics Of Critical Avalanches In Vertical Nanopillar Arrays -- 2 Quantum Chemical Study Of Point Defects In Tin Dioxide.-3 The Investigation Of The Adsorption Of Thiophene On Nimos Surface: A Density Functional Theory Study -- 4 Investigation On Control Issues In Power Converters For Advanced Micro-Grid Operations -- 5 Temporal Characteristics Of Wavelet Subbands Of Epileptic Scalp EEG Data Based On The Number Of Local Min-Max -- 6 Vibration And Reflection Reduction In Images Captured From Moving Objects Connected Through A Wireless Sensor Network -- 7 Specifying Resource-Centric Services In Cyber Physical Systems -- 8 Analyzing The Relationship Between B2b E-Marketplace Adoption And E-business Performance Using NK Simulation Method -- 9 Computing Implied Volatilities For Exchange-Traded Options On Dividend-Paying Stocks -- 10 Investigating Polling Cycle Time With Waited-Based DBA In GPONS -- 11 Island-Model-Based Distributed Modified Extremal Optimization For Reducing Crossovers In Reconciliation Graph -- 12 Early-Warning System In Bridge Monitoring Based On Acceleration And Displacement Data Domain -- 13 An Intelligent Train Marshaling Plan Of Freight Cars Considering I/O Arrangements -- 14 A Neural-Network-Based Hand Posture Recognition Method -- 15 Efficient Approach One-Versus-All Binary Tree For Multiclass SVM -- 16 Parametric Control Of National Economy$1 (Bs Growth Based On Regional Computable General Equilibrium Model -- 17 Integrating Dynamic Composition Estimation With Model Based Control For Ethyl Acetate Production -- 18 An Iterative Process For Solving The Constrained Convex Optimization Problem Via Fixed Point Methods -- 19 A Finite Difference Method For Electrostatics With Curved Boundaries -- 20 Modified Iterative Scheme For Multivalued Nonexpansive Mappings, Equilibrium Problems And Fixed Point Problems In Banach Spaces -- 21 Counting The Number Of Multi-Player Partizan Cold Games Born By Day D -- 22 Linear Programming Formulation Of Boolean Satisfiability Problem -- 23 Optimization Of Path For Water Transmission And Distribution Systems -- 24 Hierarchical Equilibrium And Generalized Variational Inequality Problems -- 25 Workforce Scheduling Using The Peast Algorithm -- 26 A New Hybrid Relaxed Extragradient Algorithm For Solving Equilibrium Problems, Variational Inequalities And Fixed Point Problems -- 27 Random Fuzzy Multiobjective Linear Programming With Variance Covariance Matrices. 28 The Different Ways Of Using Utility Function With Multi-Choice Goal Programming -- 29 A New Viscosity Cesaro Mean Approximation Method For A General System Of Finite Variational Inequalities And Fixed Point Problems In Banach Spaces -- 30 Optimal Models For Adding Relation To An Organization Structure With Different Numbers Of Subordinates At Each Level.s
Keywords: Engineering; Engineering mathematics; Engineering; Appl.Mathematics/Computational Methods of Engineering; Control, Robotics, Mechatronics; Mathematical Modeling and Industrial Mathematics; Computational Intelligence; Theoretical, Mathematical and Computational Physics